Development of 2.5D Analytical Regularization Method for reflector antenna analysis - Yucedag, Okan Mert; Turk, Ahmet Serdar (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2017)
A novel and efficient approach, which is called two-and-a-half dimensional Analytical Regularization Method (2.5D ARM), is proposed to analyse reflector antennas for microwave, millimeter wave or ultra-wide band applications. To present computational performance of the proposed method, its results are compared with well known Physical Optics (PO) and Method of Moments (MoM) solutions for a PEC hollow cylinder and an open-ended corner reflector. Moreover, radiation pattern of a ridged horn fed parabolic reflector antenna is measured to validate the method experimentally. It is observed that either the simulated or the measured data and the 2.5D ARM results are in close agreement with each other. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Analytical Regularization Method; Reflector antenna; Radiation pattern; GEOMETRICAL-THEORY; DIFFRACTION; DESIGN; Engineering; Telecommunications